Organizational Culture and Leadership Affect Nurses' Use of EMR Through Work Motivation at Hospital X Tangerang - Christine Verina; Aprilita Rina Yanti; Andry Andry (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
Electronic Medical Records (EMR) are a crucial component of hospital information systems that support the effectiveness, accuracy, and continuity of patient care. However, their implementation among nurses at Hospital X remains suboptimal due to barriers related to organizational culture, leadership, and individual motivation. This study aims to analyze the effect of organizational culture (X1) and transformational leadership (X2) on the implementation of EMR (Y) through work motivation (Z) as an intervening variable. The research applied an explanatory-causal design with a quantitative approach, using a cross-sectional survey method. Data were collected through questionnaires distributed to nurses and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that organizational culture and transformational leadership significantly influence EMR implementation both directly and indirectly through work motivation, with p-values less than 0.05. These results indicate that strong organizational values, collaborative culture, and transformational leadership that fosters motivation and innovation can improve nurses’ willingness and effectiveness in utilizing EMR. The study concludes that enhancing organizational and leadership factors, along with maintaining high work motivation, is essential to ensure successful EMR adoption and optimize healthcare service quality in hospitals.